Ergonomic Risk and Work Productivity among Manual Material Handling Workers at PT BIELOGA: A REBA-Based Analysis - Trisnanda Anugrah; Hery Irwan (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Manual material handling activities are commonly associated with awkward working postures, repetitive movements, and excessive physical load, which may increase the risk of musculoskeletal disorders and reduce work productivity. This study aims to assess ergonomic risk levels and analyze their relationship with work productivity among manual material handling workers at PT BIELOGA using the Rapid Entire Body Assessment (REBA) method. This research employed a descriptive quantitative approach. Data were collected through direct observation of workers’ postures during manual handling activities, REBA assessment, Nordic Body Map responses, and productivity measurement based on output and task completion efficiency. The findings showed that the observed manual handling activities were classified into moderate to high ergonomic risk categories, with REBA scores ranging from 5 to 9. The highest ergonomic risks were found in material loading activities and material transfer to racks, which involved trunk flexion, reaching posture, repetitive movement, and external load exposure. The analysis indicated a strong negative relationship between REBA scores and work productivity, suggesting that higher ergonomic risk tends to be followed by lower productivity performance. These findings indicate that ergonomic risk is not only related to occupational health concerns but also to operational performance. Therefore, ergonomic interventions such as workstation redesign, adjustment of material placement height, improvement of manual handling procedures, task rotation, and the use of assistive devices are recommended to reduce ergonomic risk and support productivity improvement.